Histological changes in the umbilical artery following severe chorioamnionitis and funisitis may be indicative of early atherosclerosis. (February 2017) - Rafferty, Anthony R.; D'Arcy, Colleen; Cann, Leonie; Pyman, Jan; Rogers, Peter; Davis, Peter G.; Nowell, Cameron; Burgner, David
Abstract: We investigated whether histological evidence of early atherosclerosis was present in the umbilical artery of 21 pregnancies complicated by severe perinatal inflammation, and 21 controls matched for gestational age, sex and birth weight. Severe chorioamnionitis with funisitis was associated with increased numbers of CD68 and CD45 positive cells (both P < 0.01), indicating accumulation of monocyte-derived macrophages in lesion-susceptible regions. A down-regulation of SMA expression ( P = 0.01) was also observed. These preliminary findings suggest that chorioamnionitis with funisitis may promote changes in the intima and media of the umbilical artery similar to that seen in early atherosclerosis. Highlights: The fetal aorta or umbilical artery may show features of early atherosclerosis. We investigated whether chorioamnionitis with funisitis was pro-atherogenic. CD68 and CD45 positive cells significantly increased in the umbilical artery wall. SMA expression was down regulated in the umbilical artery wall. Chorioamnionitis with funisitis may promote atherogenic changes in fetal vasculature.